Viability of piezoelectric harvesters for tire energy harvesting - Gonçalves, Pedro Miguel Pereira (2024)
The world is increasingly searching for new ways to collect energy from daily applications. Almost every road vehicle uses tires to provide optimal interaction between the car and the road surface. This quest for new methods to harvest mechanical energy from daily applications has led to increasing interest in piezoelectric materials due to their ability to generate electricity when subjected to mechanical stress. This thesis investigates the feasibility of using piezoelectric materials, embedded in the vehicle tires, to harness energy from the mechanical deformation that occurs during tire operation. Despite the limited research on this specific application, the unique properties of piezoelectric materials suggest significant potential applications for efficient tire energy harvesting. Finite Element Analysis (FEA) is utilized to model and simulate the deformation fields in an conventional truck tire, identifying optimal locations for piezoelectric materials placement. Afterward, a theoretical model is built to estimate the generated energy produced by one wheel rotation.